Subcritical water extraction of lipid containing omega-3 from microalgae Nannochloropsis gaditana - Ho, Bernard Chon Han (2020)
Omega-3 fatty acids, mainly eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) are known to have many health benefits. Many researchers have found different algal species which have high omega-3 content. Conventional techniques such as to extract microalgal omega-3 have too many disadvantages. This hinders the application of the extracted products to be fully utilized for human consumption. Therefore, a need for green, fast, and robust approach to extract the lipids from microalgae is essential. This study investigates the effectiveness of subcritical water extraction (SWE) in extracting lipid and EPA from microalgae, Nannochloropsis gaditana. The preliminary screening of SWE experiments were carried out to identify the suitable range of parameters. The highest yield of lipid for the preliminary screening was at a temperature of 210℃ and reaction time of 10 min yielding 20.79 wt% of lipid. After screening, an optimization is done with the parameters set on extraction temperature (156.1-273.9℃), time (6.6-23.4 minutes), and biomass loading (33-117 g algae/L) that are further optimized for lipid yield and EPA composition using central composite design (CCD). All three parameters were found to be significant factors for the changes in lipid yield, but extraction time was not a significant factor for EPA composition change. It was found that the predicted optimum lipid yield and EPA composition at 236.54 ℃, 13.95 minutes and 60.50 g algae/L was 18.278 wt% of total biomass and 14.036 wt% of total fatty acid methyl ester (FAME), respectively. Furthermore, the separation of the lipid extracts was performed using a solid phase extraction (SPE) method, where the lipids were classified into polar lipid (POL), neutral lipid (NL) and free fatty acid (FFA) component. From the findings, the POL was more susceptible to hydrolysis than NL. The highest recoveries of NL and POL from the biomass were 81.16 wt% and 66.45 wt% of lipid as compared to B&D method, respectively. A reaction pathway for SWE of Nannochloropsis gaditana was also developed and used to derive the kinetic equation. The highest rate constant and lowest activation energy was the pathway of algal EPA-POL to be converted into byproducts showing further that EPA-POL have high rate of hydrolysis at higher temperature with activation energy of 37.56 kJ/mol. It was also found that the model successfully incorporated to both major and minor fatty acids present in the microalgae such as palmitoleic acid, linolenic acid, and arachidonic acid. Overall, the outcome of this study contributes to a better utilization of microalgae as an available source of omega-3 fatty acids for food and pharmaceutical industry as well as achieving the green and fast extractions with high concentration of omega-3.